Role of the Prosecution in Overcoming Criminal Acts of Terrorism - Harahap, Muhammad Rafandi; Saragih, Yasmirah Mandasari; Sitorus, Tonggo; Sembiring, Ferdinand (PT. Riset Press International, 2024)
The prosecutor's office is responsible for carrying out investigations into criminal acts of terrorism. This includes collecting evidence, monitoring perpetrators, and gathering information from related parties. The prosecutor's office also has the authority to examine documents related to criminal acts of terrorism, such as newspapers, magazines, and social media. Prosecutors as Public Prosecutors have the primary task and role of prosecuting various criminal cases and carrying out judge's determinations and court decisions with permanent legal force. This terrorism case is classified as an ordinary examination procedure. The prosecution process in this terrorism case must be based on an indictment proven at a court hearing and ends with a legal charge (Requisitoir) as regulated in the Criminal Procedure Code. The procedure for criminal prosecution must be guided by the Circular Letter issued by the Attorney General's Office, namely Circular Letter Number: SE- 003/JA/8/1988, which has been updated with Circular Letter Number: SE. 001/JA/4/1995 Concerning Guidelines for Criminal Charges. The Public Prosecutor must be astute and thorough in formulating a criminal offense and the articles imposed on the defendant because it will significantly impact the indictment. If there is an error in formulating the criminal act and the articles imposed, it will have fatal consequences, namely that the case is null and void, and the defendant will be acquitted. Challenges include fulfilling formal and material requirements in the investigator's investigation report (BAP). So, the BAP has to go back and forth from the prosecutor to the investigator to be completed until it meets the requirements to be submitted to trial. There are a lot of court visitors or spectators at trials in terrorism cases. So that the prosecutor's office coordinates with the Police regarding security matters. Limitations in strengthening cooperation with related institutions in dealing with criminal acts of terrorism in the digital era.